Linguistic Forensic Analysis On Car Rental Agreement At Private Car Rental Agency - Orias, Marco; Kurniawan Zaenal, Hery (Fakultas Hukum Universitas Mataram, 2024)
Linguistic forensics can be seen as an applied linguistic science because forensic linguistics uses the application of language analysis that can include phonetics, phonology, lexigramatika, semantic discourse, and other linguistic elements for the benefit of legal processes. In its increasingly dynamic development, language analysis in forensic linguistics has a unique dimension that requires special study. This research aims to discuss aspects in the dimension of language analysis used for forensic linguistics with the main variety of writing. The discussion of the variety is associated with the language used in the lease agreement as well as the context implied in it. The discussion is also enriched with references to several studies to display the potential that can be explored more deeply. The method used in this study is the qualitative descriptive method because this research focuses on the dimensions of language analysis that are typical in forensic linguistics i.e. comparative dimension, differentiator, and gauge. It is expected that this article can contribute insight into the development of forensic linguistics research.